Chemical constituents from the roots of cratoxylum formosum and artocarpus integer and the stem of Thespesia populnea - Sompong Boonsri (Prince of Songkla University, 2011)
Thesis (Ph.D., Organic Chemistry)--Prince of Songkla University, 2010